2007
DOI: 10.1634/stemcells.2006-0662
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Cardiomyogenic Potential of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells In Vitro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 41 publications
(73 reference statements)
7
103
0
2
Order By: Relevance
“…Adult MSCs have been reported to differentiate into cardiomyocytes after treatment with 5-azacytidine 34 and soluble factors. 35 However, fully functional cardiomyocytes with striated cytoskeleton and proper electrical coupling have not been observed. We also fail to observe fully functional cardiomyocytes, but ours is the first study to demonstrate that ECM components alone significantly affect the differentiation of stem cells, even those destined to become cells of the cardiovascular system.…”
Section: Santiago Et Almentioning
confidence: 99%
“…Adult MSCs have been reported to differentiate into cardiomyocytes after treatment with 5-azacytidine 34 and soluble factors. 35 However, fully functional cardiomyocytes with striated cytoskeleton and proper electrical coupling have not been observed. We also fail to observe fully functional cardiomyocytes, but ours is the first study to demonstrate that ECM components alone significantly affect the differentiation of stem cells, even those destined to become cells of the cardiovascular system.…”
Section: Santiago Et Almentioning
confidence: 99%
“…When hUC-MSCs were treated with norm growth medium supplemented with acidic fibroblast growth factor (aFGF), sonic hedgehog (SHH), brain-derived growth factor (BDNF), nerve growth factor (NGF) and FBS and incubated at 37℃, 8% CO2, they were shown to differentiate into neurons. According to the research of Nishiyama N et al, it confirmed that hUC-MSCs can differentiate into cardiomyocyte cells using in vitro and in vivo models experiments [27] .…”
Section: Differentiation Capacities Of Huc-mscsmentioning
confidence: 95%
“…Isolation and Culture of MSCs-MSCs were isolated from UCs using the protocol developed by our group (4). Briefly, the tissue was washed with phosphate buffered saline and cut into small pieces (explants).…”
Section: Methodsmentioning
confidence: 99%
“…MSCs have proven to be a versatile source of cells capable of differentiating into various cellular lineages (1). MSCs have been isolated from a number of organs or tissues including adipose tissue (2), muscle (3), and umbilical cord (UC) (4). Our group has conducted proteome studies of chondrocytes with diverse pathologies (5,6) and has also achieved differentiation toward chondrocyte-like cells of MSCs from UC stroma using a new spheroid model and defined chondrogenic medium (7).…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%